PENGARUH CITRA MEREK, HARGA, DAN PROMOSI PENJUALAN TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE MEREK LENOVO: Studi Pada Warga Kelurahan Ciganjur Jakarta Selatan - Riyan Wahyu Pratama, - (2019)
This research is a quantitative research that aims to determine the effect of brand image, price and sales promotion on purchasing decisions of Lenovo brand smartphones. The population in this study is the community of Ciganjur Urban Village, South Jakarta. The sample size was taken as many as 75 respondents, with non probability sampling method, especially purposive sampling. Data collection is done through questionnaires. The analytical tool used is using the method of PLS (Partial Least Square) analysis. The results of this study indicate that (1) brand image has no significant effect on purchasing decisions with path coefficient values of -0.310. (2) Price has a significant effect on purchasing decisions with a coefficient of 0.441. (3) sales promotion has a significant effect on purchasing decisions with a coefficient of 0.762.